The Importance of Exercise: The Effectiveness of the Buerger Allen Exercise in Increasing Lower Limb Peripheral Circulation and Perfusion in Type II Diabetes Mellitus Patients - Dewi, Nani; Hidhayanti, Hayyu Naafi; Rakhmawati, Nur Endah; Tabarra, Sri Agustin; Lisnadiyanti, Lisnadiyanti; Kurniawan, Yani; Heriyanto, Deni (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: Type 2 diabetes mellitus can cause venous and arterial blood circulation disorders. Buerger Allen Exercise (BAE) is a modality therapy that uses active posture movements. This study aimed to assess the effect of BAE on increasing the Ankle Brachial Index (ABI) value. Methods: This study used a pre-experimental, pretest and posttest design. Sampling was carried out using consecutive sampling techniques of 54 respondents with type 2 DM. The Wilcoxon test was performed to analyze the data. Measurement of ABI values ​​was carried out to assess increased blood circulation in the legs. BAE exercises were carried out 2 times a day with a duration of 10 to 15 minutes for 3 days. In the intervention group and the control group. Results: The results showed that there was a significant difference between before and after the intervention with a p value of 0.001 (p <0.005). BAE is effective in improving blood circulation, peripheral perfusion and ABI values. Based on the results of the statistical test, it is known that p value = 0.067> 0.05 so it can be concluded that Ho: is rejected, thus it can be said that there is no difference in ABI scores in the control group. In contrast to the 10-minute BAE intervention, the test results look different with a p value = 0.0005 so it can be concluded that there is a difference between 3-minute exercise (control group) and 10-minute exercise (intervention group). Conclusion: BAE had an effect on the ABI score and had the effect of reducing peripheral vascular disease in the extremities of the legs and improving blood circulationin the legs.